2015
DOI: 10.1371/journal.pone.0129458
|View full text |Cite
|
Sign up to set email alerts
|

Post-Cranial Traumatic Injury Patterns in Two Medieval Polish Populations: The Effects of Lifestyle Differences

Abstract: Traumatic injuries can be used as general indicators of activity patterns in past populations. This study tests the hypothesis that contemporaneous (10th–12th century) rural and urban populations in medieval Poland will have a significantly different prevalence of non-violent fractures. Traumatic injuries to the post-cranial skeleton were recorded for 180 adults from rural Giecz and for 96 adults from urban Poznań-Śródka. They were statistically analyzed by body region and individual skeletal element. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
3
24
1
Order By: Relevance
“…Additionally, our study demonstrated that there was no difference in the risk of vertebral fracture between patients with a depressive disorder according to urbanization, as shown in Table 4. Previous research on patients with a traumatic fracture has claimed that the activities associated with a rural lifestyle result in more injuries and that an urban lifestyle results in a lower fracture risk 50. Another study on postmenopausal women living in rural and urban areas revealed a different perspective from that of our study, stating that rural populations experience more poverty and have lower values of vitamin D, lower BMD in the lumbar spine, and a higher prevalence of vertebral fracture and osteoporosis 42.…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, our study demonstrated that there was no difference in the risk of vertebral fracture between patients with a depressive disorder according to urbanization, as shown in Table 4. Previous research on patients with a traumatic fracture has claimed that the activities associated with a rural lifestyle result in more injuries and that an urban lifestyle results in a lower fracture risk 50. Another study on postmenopausal women living in rural and urban areas revealed a different perspective from that of our study, stating that rural populations experience more poverty and have lower values of vitamin D, lower BMD in the lumbar spine, and a higher prevalence of vertebral fracture and osteoporosis 42.…”
Section: Discussioncontrasting
confidence: 78%
“…This pattern has been extended back in time through bioarchaeological studies of fractures rates in medieval farming communities in Britain and other, globally dispersed settings (e.g., Agnew, Betsinger, & Justus, 2015;Domett & Tayles, 2006;Judd & Roberts, 1999). These studies document a range of farming activities associated with elevated rates of injury and suggest that agriculture may have introduced similarly elevated risks in the more distant past, influencing subsistence decisions and potentially shaping the trajectory of the agricultural transition.…”
mentioning
confidence: 95%
“…Modern clinical research has documented elevated rates of fracture trauma in rural farming communities in particular, frequently associated with farm equipment, encounters with livestock, and falls (Brison & Pickett, 1992;Nordstrom et al, 1995;Pickett, Brison, Niezgoda, & Chipman, 1995;Purschwitz & Field, 1990;Stallones, 1990). This pattern has been extended back in time through bioarchaeological studies of fractures rates in medieval farming communities in Britain and other, globally dispersed settings (e.g., Agnew, Betsinger, & Justus, 2015;Domett & Tayles, 2006;Judd & Roberts, 1999). These studies document a range of farming activities associated with elevated rates of injury and suggest that agriculture may have introduced similarly elevated risks in the more distant past, influencing subsistence decisions and potentially shaping the trajectory of the agricultural transition.…”
mentioning
confidence: 99%
“…However, while the diagnosis of the reason for the injuries and the cause of death can be determined, establishing the circumstances in which they happened is more difficult. Other variables need to be taken into account, some of which are not visible in the forensic examination of the skeleton as they are connected with such factors as the ways of life of the individual or population being studied: economic activities, relief of the terrain, social organisation, location of settlements and other cultural practices harder to appreciate in archaeological contexts (Scott & Buckley, 2010;Agnew et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for a correct diagnosis, aspects such as the chronological, social and cultural context of the deceased should also be analysed. All these factors contribute towards an explanation, as forensic studies and osteoarchaeological investigations have shown for materials with different origins and chronologies (Larsen, 1997;Lovell, 1997;Galloway, 1999a;Lessa, 2011;Agnew et al, 2015). Thus, it seems reasonable that the best way to approach this subject is by integrating all the contextual information, which clarifies the origin of the osseous injuries related to the death of a person.…”
mentioning
confidence: 99%